Readings in psychoanalytic psychology - Levitt, Morton, 1920- (New York : Appleton-Century-Crofts, 1959)
"This book attempts to provide in one place reliable source material for students of the behavioral sciences. It is not claimed that any single volume can contain the rich psychoanalytic lode, but it is hoped that a relatively comprehensive treatment of both the theoretical and the practical aspects of psychoanalysis will serve to point the way toward increased understanding of the purposes and practices within the field. The contributors, with the exception of Trilling, are all trained in the psychoanalytic science, and their papers are intended to reflect areas of major concern. Collateral reading lists have been appended to the articles by the editor; the student is referred also to the abundant bibliographical material provided by the authors"
Includes bibliographical references.
Keywords: Psychoanalysis; Psychoanalysis